The Relationship Between Street Skateboarders and the Need for Skateable Public Space in Bandung (Universitas Pendidikan Indonesia, 2024)
Skateboarding is an extreme sport that is quite challenging for adrenaline. Skateboarding scene lately is increasing in popularity, due to the increasing demand over time, especially in the city of Bandung. But unfortunately this is not accompanied by the addition of supporting facilities for the activists, it causes skateboarders to start taking to the streets to play using public spaces such as street sidewalks and other public facilities, which can actually be said to be less supportive for skateboarding. The writing of this journal uses quantitative methods with correlational studies. Data collection techniques using survey methods and data collection techniques using questionnaires. The results of this study are to see how the relationship between skateboarders who play on the streets and their need for supportive public spaces or commonly called 'skateables' in the city of Bandung.